Preparation and characterization of zinc oxide/ clay minerals nanocomposites as adsorbent for removal of Cu(II) and Pb(II) ions - Sani, Hannatu Abubakar (2017)
Rapid industrialization and population growth has led to the excessive release of toxic metals from agricultural and industrial activities into the environment which poses threat to ecosystem and environment in general. These toxic metals have to be effectively removed before their discharge into water bodies by economically feasible adsorbent. Clay minerals are potentially low cost materials from abundant natural resources which have the ability to accommodate new species in their structure which are of great importance in developing nanocomposites.The aim of this research is to prepare, characterize and test the adsorption efficiency of the prepared nanocomposites. In this study zinc oxide nanoparticle (ZnO-NP) was successfully incorporated into clay minerals montmorillonite (MMT) and talc by a simple green heating method using zinc nitrate and sodium alginate as zinc oxide precursor and stabilizer respectively.The prepared nanocomposites were characterized by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), Energy Dispersal X-ray (EDAX), Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM). The potentials of the prepared ZnO/MMT and ZnO/talc nanocomposites as adsorbent for the removal of copper and lead ions from their aqueous solution were investigated. The effect of the pH of the solution, adsorbent dosage, contact time, and different initial concentration on the adsorption efficiency was studied systematically. The pseudo-first-order and pseudo-second-order kinetic models were used to describe the kinetic data while Langmuir andFreundlichwere used for the isotherm. XRD and FESEM analyses revealed the presence of ZnO nanoparticles with hexagonal wurtzite structure in the nanocomposites.Energy dispersive X-ray (EDX) also confirmed the presence of ZnO nanoparticles in the nanocomposites. The percentage removal of by ZnO/MMT was found to be 97.2% (Pb) and 89.5% (Cu) which are higher than that of 90.3% (Pb) and 80.6 % (Cu) for ZnO/talc. Kinetics studies revealed that the adsorption of Cu(II) and Pb(II) onto the prepared anocomposites followed the pseudo-second order kinetics. The adsorption equilibrium data fitted well to Langmuir isotherm model.Maximum adsorption capacities for the ZnO/MMT and ZnO/talc at pH of 4 were 88.50 and 48.30 mg/g for Pb(II) and 54.06 and 83.30 mg/g forCu(II), respectively.The regeneration revealed that the nanocomposites adsorbent can be utilized for more than three times. They can serve as promising adsorbents for the removal of Cu(II) and Pb(II)lead ions from aqueous solutions because of their distinctive chemical and physical properties.Electrostatic attraction and ion exchangecould be the main adsorption mechanisms for lead and copper ions adsorption onto the nanocomposites. Thermodynamics results revealed that the adsorption was an exothermic process. The experimental results showed that the nanocomposites have high level of adsorption towards heavy metal ions. Consequently, it is concluded that the prepared nanocomposites (ZnO/MMT and ZnO/talc) can be used for the removal of the heavy metal ions from the aqueous solutions.